Heat, quantum mechanics and information - Khumalo, Bhekuzulu (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Heat has often been described as part of the energy transfer process. Information theory says everything is information. If everything is information then what type of information is heat, this question can be settled by the double slit experiment, but we must know what we are looking for.